Dietary complementation across life stages in the polyphagous lady beetle Coleomegilla maculata - Michaud, J. P.; Jyoti, J. L. (My University, 2012)
We investigated the life history consequences of changes in diet between larval and adult life stages in the polyphagous lady beetle Coleomegilla maculata DeGeer (Coleoptera: Coccinellidae). Beetles were reared on three larval diets: greenbug, Schizaphis graminum Rondani (Homoptera: Aphididae), eggs of the flour moth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae), and bee pollen. The reproductive performance of females was then evaluated on an adult diet of either greenbug or moth eggs. Moth eggs appeared to be the most suitable diet for larvae, yielding the largest adults, and pollen the least suitable, resulting in the smallest adults and greatly extended developmental time. Pollen-reared beetles tended to have lower fecundity and fertility than those reared on animal protein, regardless of adult diet. Female fitness was generally increased by a change in diet upon emergence to the alternative source of animal protein, suggesting that dietary complementation occurred across life stages. Among females reared on greenbug, a change of diet to moth eggs reduced the period required for production of 12 clutches and increased egg fertility compared to continued feeding on greenbug. Among females reared on moth eggs, a change of diet to greenbug increased fecundity compared to continued feeding on moth eggs. Among females fed an adult diet of greenbug, those fed moth eggs as larvae had faster production of 12 clutches and higher fecundity. We discuss these novel results in the context of coccinellid life history and ecology and their potential implications for other insects that are predatory as both larvae and adults.
Citation: Michaud, J.P., & Jyoti, J.L. (2008). Dietary complementation across life stages in the polyphagous lady beetle Coleomegilla maculata. Retrieved from http://krex.ksu.edu
Keywords: Coccinellidae; Coleoptera; Development; Ephestia kuehniella; Fitness; Pollen; Reproduction; Schizaphis graminum